Diplomatic Collaborative Solutions to Assure the Adoption of the European Single Market Amid the COVID-19 Pandemic - Logar, Silvia; Alessandro, Rizzardo (Frontiers in Public Health, 2021)
As the COVID-19 crisis has shown, the lack of harmonized and coordinated actions superseding national borders represented a limit to the full implementation of already existing legal binding instruments at the European level. It is recognized that the existing levels of globalization have contributed to accelerate the large-scale transmission of viruses and increased the likelihood of a pandemic public health crisis. This article aims to highlight the importance of greater bilateral cooperation to mitigate the health and economic impact of the coronavirus disease 2019 (COVID-19) pandemic. It focuses on the implementation of diplomatic collaborative systems to assure the full implementation of the European single market as well as the adoption of standardized health information platforms as a part of pandemic preparedness and control measures.